2021
DOI: 10.13181/mji.oa.215674
|View full text |Cite
|
Sign up to set email alerts
|

Perception and preventive behavior during COVID-19 pandemic among urban residents in Banda Aceh, Indonesia: a cross-sectional study

Abstract: BACKGROUND It is critical to evaluate the perception and preventive behavior of COVID-19 to formulate the optimal public health strategies for tackling the ongoing pandemic. This study aimed to enhance knowledge on the perception and preventive behavior toward COVID-19 among urban residents in Banda Aceh, Indonesia. METHODS A cross-sectional population-based survey was conducted from September to October 2020 using a structured questionnaire for the attendants of the six public health centers in Banda Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
5
1
2
Order By: Relevance
“…However, a study in Bangladesh found that people with no formal education had lower performing preventive COVID-19 behaviors (Hosen et al, 2021 ). In accordance with an Indonesian study, people who had higher educational levels were more inclined to engage in good preventive behavior (Husnah et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, a study in Bangladesh found that people with no formal education had lower performing preventive COVID-19 behaviors (Hosen et al, 2021 ). In accordance with an Indonesian study, people who had higher educational levels were more inclined to engage in good preventive behavior (Husnah et al, 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…Comorbidity diseases were not associated with face mask wearing, in contrast to the finding in an Indonesian study that urban residents with the underlying diseases had poor preventive behavior (Husnah et al, 2021). In addition, people with underlying diseases in Iran had higher levels of fear of COVID-19 (Mosazadeh et al, 2021), and it is due to the COVID-19 behavioral awareness.…”
Section: Discussioncontrasting
confidence: 75%
“…However, those with a low-risk perception of COVID-19 are less likely to engage in protective behavior. Thus, public health education is targeted at this group 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Masa pandemi COVID-19 dimulai dari adanya penyebaran virus pada bulan Desember tahun 2019 di Wuhan, China dan dinyatakan sebagai pandemi pada Januari 2020. COVID-19 di Indonesia telah berlangsung sejak bulan Maret 2020 [1] Penambahan kasus terkonfirmasi kembali meningkat secara drastis sejak bulan Januari 2022. Banyaknya informasi yang tidak tepat mengenai COVID-19, seperti melalui media sosial, menyebabkan banyak kebingungan dan menimbulkan persepsi yang berbeda-beda di kalangan masyarakat mengenai apa yang harus dilakukan agar tidak terpapar virus SARS-CoV-2.…”
Section: Pendahuluanunclassified